The Influence of Extrinsic Motivation on Bank Employee Performance in Karnali Province (Quest Journal of Management and Social Sciences, 2025)
Background: Employee performance is a crucial determinant of organisational success, significantly impacting productivity, profitability, and overall business outcomes by driving operational efficiency and competitive advantage in the marketplace.Purpose: This study aims to investigate the impact of extrinsic motivational factors on employee performance in the banking sector of Karnali Province, Nepal. Four key extrinsic factors are examined: rewards and recognition, interpersonal relationships, job security, and working conditions.Methods: This study uses descriptive and causal comparative research designs. The study population consists of all banking industry employees working in the different branches and province-level offices of Karnali province. A structured questionnaire was self-administered to gather data from 340 employees employing the convenience sampling strategy. Pearson's correlation coefficient was used to evaluate the relationships between these factors and employee performance. Regression analysis assessed the predictive power of these factors on performance.Findings: The results showed a significant positive relationship between all four extrinsic motivational factors and employee performance. Rewards and recognition were strong motivators, as employees who felt valued and appreciated performed at higher levels. Positive interpersonal relationships contributed to better communication, teamwork, and overall job satisfaction, boosting performance. Job security was crucial, as employees who felt secure in their positions showed greater dedication and engagement.Conclusion: Thus, the study concludes that rewards and recognition, interpersonal relationships, job security, and working conditions influence employee performance in the study area. The study emphasises the importance of addressing extrinsic motivational factors in the workplace. Organisations can significantly enhance employee performance and organisational outcomes by focusing on rewards and recognition, fostering strong interpersonal relationships, ensuring job security, and improving working conditions.Keywords: Employee Performance, Rewards and Recognition, Interpersonal Relationships, Job Security, and Working ConditionsJEL Codes: J24, M12, M54, J28